Free and open source software as global public goods? What are the distortions and how do we address them?. Issue 4 (8th February 2019) - Sahay, Sundeep
Abstract: Promoting software as global public goods (GPGs) is an important element of the development agenda. This strategy is especially relevant for the public health sector in developing countries, where the landscape of past information and communication technology (ICT) initiatives are littered with stories of failures, contributed significantly through the use of proprietary software and associated vendor lock‐ins. This paper examines the GPG characteristics of nonexclusivity and nonrivalry and how these apply to software. Taking these characteristics as normative ideals, which we should strive to achieve in furthering our development agendas, we examine what are the "distortions" to achieve them. Understanding these potential distortions can help in materializing the potential benefits of free and open source software. These arguments are illustrated through the case of trying to implement the open source DHIS2 software in the public health sector in India.